The influence of proficiency level on the use and choice of L1/L2 communication strategies used by Iraqi EFL students - Raed Latif Ugla; Mohamad Jafre Zainol Abidin; Mohammed Najim Abdullah (International Journal of Evaluation and Research in Education (IJERE), 2019)
This study aimed at investigating the influence of language proficiency level on the frequency of the use and choice of L1/L2 communication strategies used by Iraqi EFL students. This study was qualitative in nature. The interactive task and speaking task were used to gather data regarding communication strategy use and choice from 52 second and third year English major students. Those participants were divided into two groups; low and high proficient students (n=27 low proficient students and n=25 high proficient students). A taxonomy of communication strategies was adopted to code the communication strategies used by low and high proficient Iraqi EFL students. The results revealed that low proficient students use communication strategies more frequently than high proficient students. Both low and high proficient students used communication strategies other than those included in selected taxonomy. This study showed that low proficient students use L1-based strategies more frequently, while high proficient students use L2-based strategies more frequently.